Estimasi potensi biomassa permukaan, stok karbon, dan produksi oksigen berdasarkan keragaman jenis pohon di ruang terbuka hijau (RTH) Kabupaten Jombang - Utomo, Djagad Fajar; Baskara, Medha (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2026)
Jombang Regency is one of the strategic areas in East Java that still contributes to carbon emissions, making green open spaces (GOS) with tree vegetation essential for mitigating climate change. This study aimed to identify tree species diversity and estimate aboveground biomass, carbon stock, carbon dioxide absorption, and oxygen production in four GOS areas in the form of city parks in Jombang Regency, as well as to analyze the influence of tree characteristics such as height, trunk diameter, number of individuals, and wood density on their environmental contributions. The research was conducted in Mojoagung Park, Kebonratu Park, Kebonrojo Park, and Alun-alun Jombang using a direct survey method and non-destructive allometric estimation. The data collected included tree species identification, height and diameter measurements, and biomass and carbon calculations based on the condition of the tree. Results showed a total of 1.005 trees from 56 species, with a moderate diversity range 1,81 to 2,72 and a high evenness index range 0,71 to 0,83. Kebonratu Park had the highest contributions to carbon absorption and oxygen production, followed by Kebonrojo Park, Alun-alun Jombang, and Mojoagung Park. The vegetation structure and composition of each GOS influenced the variations in contributions. The study concluded that tree characteristics significantly affect carbon absorption and oxygen production potential, making them a vital basis for ecological and sustainable GOS management recommendations.